Answer:
B- False
Step-by-step explanation:
Answer:
8 in^2.
Step-by-step explanation:
F = P * A
22 = 2.75 * A
A = 22/ 2.75
A = 8 in^2.
Y = mx + b. Use this equation for most linear functions. Enter the information that is given to you.
![- 6 = - 3(4) + b](https://tex.z-dn.net/?f=%20-%206%20%3D%20%20-%203%284%29%20%2B%20b)
Multiply the -3 and 4 to get 12.
![-6 = - 12 + b](https://tex.z-dn.net/?f=%20-6%20%3D%20%20-%2012%20%2B%20b)
Now divide the -12 from both sides.
![\frac{ - 6}{ - 12} = \frac{ - 12}{ - 12} + b](https://tex.z-dn.net/?f=%20%5Cfrac%7B%20-%206%7D%7B%20-%2012%7D%20%20%3D%20%20%20%5Cfrac%7B%20-%2012%7D%7B%20-%2012%7D%20%20%2B%20b)
-12 cancels out on the right side and your left with
![- \frac {1}{2} = b](https://tex.z-dn.net/?f=%20%20-%20%5Cfrac%20%7B1%7D%7B2%7D%20%20%3D%20b)
Now re-enter the info back into the formula.
![y = - 3x - \frac{1}{2}](https://tex.z-dn.net/?f=y%20%3D%20%20-%203x%20%20-%20%20%5Cfrac%7B1%7D%7B2%7D%20)
Then you've got your formula
Pounds of beef and potatoes are in ratio or proportion of
.
<u>Step-by-step explanation:</u>
Correct Question: A recipe for beef stew calls for 1 pound of beef and 3 potatoes. The recipe is doubled to include 2 pounds of beef and 6 potatoes. Which proportion represents the situation?
We have , A recipe for beef stew calls for 1 pound of beef and 3 potatoes , i.e.
Number of beef stew calls = 1
Number of potatoes = 3
Now , The recipe is doubled to include 2 pounds of beef and 6 potatoes i.e. for every 2 pounds of beef we have 6 potatoes
⇒ ![2/6](https://tex.z-dn.net/?f=2%2F6)
⇒ ![\frac{2}{6}](https://tex.z-dn.net/?f=%5Cfrac%7B2%7D%7B6%7D)
⇒ ![\frac{2}{2(3)}](https://tex.z-dn.net/?f=%5Cfrac%7B2%7D%7B2%283%29%7D)
⇒ ![\frac{1}{3}](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7B3%7D)
Therefore , Pounds of beef and potatoes are in ratio or proportion of
.
This may look a little confusing but all you have to do is plug the equation given for h(x) which is 2x-5 in to the h(x) area in the equation where it says h(x) + g(x).
So far that’s (2x-5) + g(x)
Then,
Do the same with equation given for g(x) which is now,
(2x-5) + (3x+1)
Then solve,
2x - 5 + 3x + 1
2x + 3x- 5 + 1
5x - 4
Therefore the answer is 5x - 4.